Soil and water losses under crop-forest integration and in soybean-corn succession - Zolin, Cornélio Alberto; Paulino, Janaina; Matos, Eduardo da Silva; Magalhaes, Ciro Augusto de Souza; Almeida, Frederico Terra de; Souza, Adilson Pacheco de; Mingoti, Rafael (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate, under conditions of natural rainfall, the soil and water losses in crop-forest integration systems or in soybean-corn succession. The experiment was carried out in a clayey Latossolo Vermelho-Amarelo (Oxisol), in a Cerrado/Amazon transition region. The following land use and soil covers were evaluated: crop-forest integration system; soybean-corn+brachiaria succession system; and bare soil. Crops were cultivated under no-tillage in soybean-corn+brachiaria sucession, every year, regardless of the production system. In the three years of evaluation, soil losses by hydraulic erosion were of 0.215 Mg ha-1 per year, in the crop-forest integration system, and of 0.753 Mg ha-1 per year, in the soybeancorn succession system. These values were below the tolerance limit, which is of 11.1 Mg ha-1 per year, and the lowest values for crop-forest integration point towards the great conservation potential of this production system.